lncRNA UCA1 Functions as a ceRNA to Promote Prostate Cancer Progression via Sponging miR143 - Yu, Yanlan (Mol Ther Nucleic Acids, 2019)
UCA1 (urothelial carcinoma associated 1) is a long non-coding RNA (lncRNA) that was found overexpressed in various human cancers including prostate cancer (PCa). However, the aspect of UCA1-miRNA-mRNA interaction in PCa remains unclear. In this study, we confirmed the role of UCA1 in PCa and found that UCA1 downregulation inhibited cell proliferation of PCa cells. Then we demonstrated that repressed UCA1 promoted the microRNA-143 (miR-143) expression and miR-143 could bind to the predicted binding site of UCA1. We then proved the anti-tumor role of miR-143 in PCa. Furthermore, we found that miR-143 displays its role in PCa via modulating the MYO6 expression. In summary, our study demonstrated that UCA1 exerts oncogenes activity in PCa, acting mechanistically by upregulating MYO6 expression through “sponging” miR-143.